KONSEP FIDUSCIAIRE EIGENDOMS OVERDRACHT DALAM KAJIAN FIQH MUAMALAH - HAK, Nurmala; Yuswalina, Yuswalina (Nurani, 2019)
In Civil Law, a fiduciary guarantee is an agreement whereby the debtor binds its agreement to the creditor for the debt payable which makes proof of ownership of an object to be used as collateral for its debt. The agreement that occurs in a fiduciary guarantee called the accession agreement (additional agreement) is not the principal agreement of a loan agreement, to fulfill the achievements among the parties; the fiduciary guarantee must be registered with the fiduciary Registration Office. Whereas the fiduciary concept in Muamalah Fiqh according to the General Provisions of Fatwa DSN-MUI No. 68 / DSN-MUI / III / 2008 About Rahn Tasjily Fidusia is analogous to Rahn Tasjily. The concept of rahn tasjîly the râhin party binds the agreement to the murtahin, which is called the rahn tasjîly agreement by using a debt debt agreement accompanied by a collateral / guarantee in the form of evidence of ownership submitted to the murtahin. This means that the agreement contained in rahn tasjîly is an agreement that is accesoir because collateral in a debt in rahn tasjîly is an additional agreement. The difference between fiduciary guarantees and rahn tasjîly can be seen in terms of maintaining objects. In a fiduciary guarantee, the maintenance of objects that are used as collateral for debt is the obligation of the creditor but the maintenance costs are the responsibility of the debtor. Whereas in rahn tasjîly the maintenance of objects that are used as collateral for debt is not only the obligation of rahin, but can also be carried out by murtahin, while the equality can be seen from various aspects both in terms of definition, object, form of agreement, termination of agreement, and manner of execution goods. One of them is in terms of objects, fiduciary and rahn tasjîly guarantees that are the same as collateral for debt not the form of an object, but proof of ownership of the object. Keywords: Jaminan, fidusia, rahn, tasjîly.